Predictors of cultural adjustment among international students in Malaysia: counseling implications - Ssekamanya, Siraje Abdallah (2012)
In the Educational Development Plan 2001 to 2010, the Ministry of Education Malaysia set the ambitious goal of attracting 100,000 international students by 2010 as one of the milestones of turning Malaysia into a center of excellence in higher education. By the end of 2011, Malaysia had indeed managed to attract almost 100,000 foreign students from more than 100 countries. It is time now to move beyond the numbers and consider the quality of the students and the quality of their experiences in Malaysia. The present study focused on the cultural adjustment of foreign students in Malaysia: what challenges they face in adjusting to the host culture? What factors have helped them to cope with those challenges? What implications does this have on the provision of guidance and counseling services in Malaysian universities and colleges? The study draws upon the model of cultural adjustment proposed by Ward, Furnham, and Bochner (2001).